2006
DOI: 10.7589/0090-3558-42.4.819
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sin Nombre Virus Antibody Prevalence in Deer Mice Across Seasons: The Interaction Between Habitat, Sex, and Infection in Deer Mice

Abstract: ABSTRACT:We examined the impact of season and habitat on Sin Nombre virus (SNV) seroprevalence in deer mice (Peromyscus maniculatus) in Utah's Great Basin Desert from May 2002 through summer 2003. Low mouse captures in 2002 limited analysis for that year. In two seasons during 2003, mouse density and sagebrush cover were positively linked (spring: r50.8, P50.01; summer: r50.8, P50.04). In the spring, seroprevalence was negatively correlated with density (r520.9, P,0.01); male and female antibody prevalence did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Over the 14 years of our study, we were able to access trapping grids each month, even when environmental conditions, such as deep snow, made site access and trapping challenging. Although trapping in winter is not always possible due to inaccessibility of trapping locations (e.g., Douglass et al 2001, Pearce-Duvet et al 2006), investigators should recognize that the detection of annual highs in host abundance and infection is reduced when sampling is less frequent than monthly, and when sampling is not undertaken during winter. Nevertheless, this study suggests that annual highs in deer mouse MNA are most frequently detected between August and October and ESP between April and August, likely reflecting a delayed transmission relationship between deer mouse abundance and infection (Madhav et al 2007).…”
Section: Sampling Frequency and Host-pathogen Dynamicsdiscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the 14 years of our study, we were able to access trapping grids each month, even when environmental conditions, such as deep snow, made site access and trapping challenging. Although trapping in winter is not always possible due to inaccessibility of trapping locations (e.g., Douglass et al 2001, Pearce-Duvet et al 2006), investigators should recognize that the detection of annual highs in host abundance and infection is reduced when sampling is less frequent than monthly, and when sampling is not undertaken during winter. Nevertheless, this study suggests that annual highs in deer mouse MNA are most frequently detected between August and October and ESP between April and August, likely reflecting a delayed transmission relationship between deer mouse abundance and infection (Madhav et al 2007).…”
Section: Sampling Frequency and Host-pathogen Dynamicsdiscussionmentioning
confidence: 99%
“…The use of infrequent sampling (i.e., seasonal or semiannual) to monitor population abundance of small mammals, such as deer mice, is common (e.g., Saitoh et al 1999, Strann et al 2002, Flowerdew et al 2004, Larsen et al 2007. In some instances studies using infrequent sampling of small mammals also extend to examination of wildlife (e.g., Cavanagh et al 2004) or zoonotic pathogens (e.g., Carver et al 2008) among individuals comprising reservoir populations, such as for hantaviruses in their rodent hosts (Biggs et al 2000a, 2000b, Escutenaire et al 2000, Olsson et al 2003, Pearce-Duvet et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to biting and aggression between individuals, aerosol transmission is also considered a significant mode of transmission between rodents [11,83,84,85,86,87]. Some viruses, such as the virus Sin Nombre, appear to be directly transmitted by bodily fluids, particularly during aggressive encounters and possibly during “allogrooming” (cleaning and licking between different individuals in a colony) [61,88]. However, many hantaviruses (PUU, SEO, BCC, HTN) are transmitted indirectly between hosts by inhalation of contaminated feces [84,89,90,91].…”
Section: Hantavirus Hostsmentioning
confidence: 99%
“…Although there is no evidence of vertical transmission, some studies have suggested the existence of more than one source of horizontal transmission, as described above, which may vary depending on the behavior of the natural hosts, the virus type and the ecosystem in which the rodents and virus circulating. In the natural environment, the seroprevalence among rodents typically increases with weight (relative age marker) and age, emphasizing the role of horizontal transmission in maintaining the virus within rodent populations [84,86,88]. Moreover, the high prevalence among males and the presence of injuries in some of the males highlight transmission via aggression and biting, which could occur during territorial disputes [35,85,86].…”
Section: Hantavirus Hostsmentioning
confidence: 99%
“…For example, the PUUV prevalence in rodents seems to be quite different depending on time, region and the local hantavirus outbreak situation (Essbauer et al 2006;Mertens et al 2011b;Augot et al 2008). Hantavirus infections in rodents are chronic and may have an impact on the population levels and the physiological status (Pearce-Duvet et al 2006;Tersago et al 2008Tersago et al , 2012Luis et al 2012). …”
Section: Do Hantavirus Infections Have An Impact On Animals?mentioning
confidence: 99%